Supermassive black holes from OASIS and SAURON integral-field kinematics - Cappellari, M; Bacon, R; Davies, R; De Zeeuw, P; Emsellem, E; Falcón-Barroso, J; Krajnović, D; Kuntschner, H; McDermid, R; Peletier, R; Sarzi, M; Van Den Bosch, R; et al. (2007)
Supermassive black holes are a key element in our understanding of how galaxies form. Most of the progress in this very active field of research is based on just ~30 determination of black hole masses, accumulated over the past decade. We illustrate how integral-field spectroscopy, and in particular our OASIS modeling effort can help improve the current situation. © 2008 Copyright International Astronomical Union 2008.